2016
DOI: 10.1186/s12886-016-0283-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the in-the-bag stabilities of single-piece and three-piece intraocular lenses for age-related cataract patients: a randomized controlled trial

Abstract: BackgroundTo compare the in-the-bag stability and visual function of single-piece intraocular lenses (IOLs) and three-piece IOLs.MethodsA total of 65 patients with age-related cataracts (80 eyes) were enrolled and randomly assigned to receive in-the-bag implantation of either a single-piece IOL (40 eyes) or a three-piece IOL (40 eyes). Follow-up visits were conducted at 1 week, 1 month and 3 months postoperatively. Visual acuity, refraction and total aberration were examined. IOL position stability (including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
(17 reference statements)
0
13
0
1
Order By: Relevance
“…In multifocal IOLs, decentration might result in a different light distribution between the distance focus and near focus [ 18 ]. With regards to IOL design, 1-piece and 3-piece, hydrophobic and hydrophilic IOLs have been reported to perform equally well in terms of decentration and tilt [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In multifocal IOLs, decentration might result in a different light distribution between the distance focus and near focus [ 18 ]. With regards to IOL design, 1-piece and 3-piece, hydrophobic and hydrophilic IOLs have been reported to perform equally well in terms of decentration and tilt [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhong reported 1-piece IOLs exhibits better axial stability and more stable refractive outcomes after three months in the bag. 11 …”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the IOLs implanted in the capsular bag effect anterior segment parameters by the time. 11 Design of the IOL (i.e., whether it is 1-piece or 3-piece model) may be the most important characteristic. Haptic of the 1-piece IOLs have the same material with optics and they are in soft manner.…”
Section: Introductionmentioning
confidence: 99%
“…Chang 15 found that the silicone plate haptics have a higher incidence of rotation than hydrophobic C-loop. Zhong et al 16 found that single-piece IOLs exhibit better axial stability and more stable refractive outcome than three-piece IOLs. Rotation occurs most frequently in the early postoperative period, before anterior and posterior capsules fuse together with the lens.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods to measure IOL decentration and tilt once it is implanted inside the pseudophakic eyes. These include slit lamp assessment, 21 retroillumination photography, 22 Scheimpflug imaging, 16 optical coherence tomography, [23][24][25] and measurements using Purkinje reflections. [26][27][28] But before the implant injection into the eye, a study on reliable prediction of the visual outcome of the implantation needs to be performed.…”
Section: Introductionmentioning
confidence: 99%